Berjuang untuk Agama dan Bangsa: Biografi Kiai Haji Noer Ali, 1914-1992 - Nur Fadillah Tamala; Arifin Silaban; Benzisno Josua Simanjorang; Tappil Rambe (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
The formation of Bekasi Regency began when Bekasi residents tried to reject the existence of the United States of Indonesia or RIS. Bekasi residents demanded that the Unitary State of the Republic of Indonesia be re-established and opposed the existence of Pasundan. This effort made Bekasi people's leaders, one of which was Kiai Haji Noer Ali, took part and played a role in changing the name of Bekasi Regency. Kiai Haji Noer Ali also played a role in fighting for the Bekasi Regency area to establish the At-Taqwa Islamic Boarding School. The method used in this study is the Historical Method which consists of four stages, with the data collection technique being a literature study. Literature research or literature study is a stage related to the method of collecting, reading and recording and processing library data as research material. The results of this study describe the educational background of Kiai Haji Noer Ali and his efforts in defending the land of Bekasi from the Dutch side to successfully build At-Taqwa Islamic Boarding School.